Edukasi dan Promosi Kesehatan Diabetes Melitus Lingkungan XIX Kelurahan Tanjung Mulia Hilir Kecamatan Medan Deli - Syahrul Handoko Nainggolan; Ali Asman Harahap; Candra Damanik (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
Education and health care for diabetes mellitus in Environment Objective: This implementation is to increase knowledge and health care about diabetes mellitus in Environment XIX, Tanjung Mulia Hilir Village, Medan Deli District. Health promotion for diabetes mellitus (DM) focuses on empowering individuals and communities to make sustainable lifestyle changes that prevent or delay the onset of type 2 diabetes and effectively manage existing diabetes to minimize complications. This method involves a multifaceted approach that includes: 1). Prevention, namely increasing awareness by educating the public about diabetes risk factors (such as obesity, lack of physical activity, unhealthy eating patterns, family history) and promoting healthy lifestyle choices. Encourage regular screening for early diagnosis, especially for those with risk factors. Promote healthy eating habits, regular physical activity, and maintaining a healthy weight. Expected Outcome: increasing public awareness of diabetes risk factors (such as obesity, lack of physical activity, unhealthy diet, family history) and promoting healthy lifestyle choices. As well as the existence of guidelines for healthy eating and physical activity. Mechanisms for solving problems and overcoming them.